Nietzsche y Sloterdijk: Depauperación del nihilismo, posthumanismo y complejidad extrahumana - Vásquez Rocca, Adolfo (Nómadas. Critical Journal of Social and Juridical Science, 2010)
For Nietzsche, nature is broken figures and, in a continual creative process in that succeeds the vital, full of power. Survival does not mean yet success. Life triumphs in profusion, when is wasted when living with exultation. The live acts subjugation. It is an energetic process and as such "meaningless" because it is not directed at any higher purpose. Nietzsche presents his doctrine as an overcoming of nihilism through its completion. Nietzsche’s concern revolves around the increasingly overwhelming nihilism, when men experience a "mortal fatigue of living", a bleak perception of the vanity of all efforts, the men come to pessimism about life and following a trend-ascetic - waive it. It is the recognition of the abandonment of self, a reflexive and negative abandonment, which becomes the basis of ethical rigor and ontological matrix of sacrifice.